Decision on breast reconstruction in women after mastectomy – motivation, concerns, effects’ perception - Brandt, Anna; Przybyła-Basista, Hanna (Psychoonkologia, 2016)
Introduction: Breast subtraction is a source of severe stress, sense of shame and fear associated with the loss of attractiveness in women suffering from breast cancer. This is sometimes called by the researchers “the half woman complex”. Aim : The objective of this paper is to compare the motivation and concerns connected with the decision on breast reconstruction of women after mastectomy who underwent breast reconstruction, with women after mastectomy, who decided not to do it. In the first group the level of satisfaction with the cosmetic effect of surgery was also investigated. Material and methods : The sample consisted of 97 women after mastectomy, including 25 who had undergone breast reconstruction and 72 who had not. To explore variables like motivation, fears and perceptions of the effects of breast reconstruction a questionnaire developed by the authors was used. Results : We have found that for women who did not opt for breast reconstruction the arguments related to anxiety (fear of pain, another surgery) were important. In the other group women’s motivation for breast reconstruction was more individual in nature and the women in this group generally reported satisfaction with the aesthetic effects of breast reconstruction. Some differences between the two groups were noted: women with breast reconstruction confirmed loss of self-acceptance as a leading concern about mastectomy, while women after mastectomy reported loss of self-attractiveness. Conclusions : It can be concluded that women’s motivation for breast reconstruction results from an increased focus on themselves due to illness, feeling of injury, and a sense of desire to increase self-acceptance.